Violência sexual e discriminação racial: influência na responsabilização da vítima - Albuquerque, Iara Maribondo (2015)
This work aims to investigate whether the woman's skin color and the attacker's skin color influence the responsibility attributed to the woman for the violence she suffered. Therefore, three main hypotheses were formulated that guided the conduct of three empirical studies. Study 1 tested the following hypotheses: the black female victim of sexual violence will be seen as more responsible than the white female victim, and the victims will be seen as more responsible when the attacker is black. The participants were 200 college student volunteers with a mean age of 20.70 years (SD = 4.00; 99 men and 101 women), who were separated into each the four experimental conditions (photos of a black man and a white woman; photos of a white man and a black woman; photos of a black man and a black woman; and photos of a white man and a white woman). As a result it was observed that when the attacker is black, the white victim (M = 3.83, SD = 0.29) is seen as more responsible than the black victim (M = 2.87, SD = 0.26 ). Thus the first hypotheses were not confirmed, as contrary to expectations, the results indicate that the attacker's skin color influences the responsibility assigned to the victim. Since the participant's gender did not have any influence on these results, the hypothesis was raised that the professional context of the participants could influence the responsibility assigned to the woman for violence she suffered. Thus, Study 2 aimed to investigate whether the male and female occupational classification (Carvalho, 2003) remained in force in order to test this hypothesis in Study 3. The participants in Study 2 were 100 college students with a mean age of 21.66 years (SD = 3.53; 48 men and 52 women). The results indicate that the classification is still in force today, considering disciplines such as engineering, computing, physics, and mathematics as professions better performed by men, and nursing, nutrition, and pedagogy as disciplines considered feminine. Finally, Study 3 sought to test the third hypothesis that the participant's group membership (female vs. male courses of study) would alter the responsibility assigned to the victim. With the participation of 202 college students with a mean age of 21.51 years (SD = 5.17; 101 men and 101 women) it was found that there is a significant triple interaction effect between the victim's skin color, the skin color of the aggressor, and the participant's group membership, confirming the hypothesis raised. Thus, in the female courses of study, when the victim was white and the attacker black, she was found more responsible (M = 3,86, SD = 0,30) than in the other experimental conditions.